2011
DOI: 10.1097/scs.0b013e3182087378
|View full text |Cite
|
Sign up to set email alerts
|

Craniometric and Velopharyngeal Assessment of Infants With and Without Cleft Palate

Abstract: Results from the current study are in agreement with previous studies demonstrating variations across patients with cleft palate particularly in the muscle bundle lengths, distance between muscle origins, velar thickness, and velar length. Longitudinal studies are needed to determine how levator muscle and craniometric dimensions vary between those with and without cleft palate. A larger sample size is necessary to provide statistical analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 6 publications
8
36
0
Order By: Relevance
“…The LVP of infants is approximately two-thirds of the length of the LVP of adults. 13,20,24,25 This suggests that scaling down the simulated overlap distances for surgeries on infants and children would produce the same mechanical effects on closure force. Estimated overlap amounts for adults and infants based on the overlap percentages from this study are shown in Table 2.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The LVP of infants is approximately two-thirds of the length of the LVP of adults. 13,20,24,25 This suggests that scaling down the simulated overlap distances for surgeries on infants and children would produce the same mechanical effects on closure force. Estimated overlap amounts for adults and infants based on the overlap percentages from this study are shown in Table 2.…”
Section: Discussionmentioning
confidence: 91%
“…24 One could argue that there should be a wide range of total LVP lengths due to a wide range of cleft severities and anatomies. For example, in a case with a very wide cleft, the LVP may be attached more anteriorly within the mouth, so that the origin and insertion of muscle would be farther apart, making the muscle longer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The average angle at the origin, between the base of the skull and the course of the muscle bundle during rest, was 64.5° for women and 60.4° for men. Levator muscle thickness has been reported in several studies (Ettema et al, 2002; Ha et al, 2007; Perry et al, 2011; Perry, 2011), although some have questioned the validity of these reports (Ha et al, 2007). This is because studies using magnetic resonance imaging have measured the diameter using a two-dimensional image plane.…”
Section: Introductionmentioning
confidence: 99%